Sewage - Zhu, Ivan X. (IntechOpen, 2018)
Wastewater treatment and sludge disposal are important for protecting receiving rivers, lakes, and other water bodies, and vital for human health. Since excessive discharge may cause eutrophication and deterioration of aquatic systems, the US EPA and other national agencies have set guidelines for wastewater discharge standards. Conventional technologies are well developed and widely applied worldwide for wastewater treatment; however, new ideas and new technologies are gaining additional interest for the sake of water and energy reuse. While water is essential in arid regions, wastewater reuse and recycling have been playing an important role in human life. Although there are no universal standards for industrial and agriculture reuse, balancing wastewater treatment and public health protection presents challenges and opportunities.